Preparation method and application of mesoporous titanium oxide-supported high-content cobalt single-atom catalyst

Through the preparation of a mesoporous titanium oxide-supported cobalt single-atom catalyst, the catalytic performance is improved by using the sol-gel method, the efficiency and stability of existing catalysts in the treatment of antibiotic-contaminated water bodies is solved, and the sulfasalazine is realized The efficient degradation of pyridine has good environmental friendliness and application prospects.

CN116212876BActive Publication Date: 2025-01-14EAST CHINA UNIV OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310353198.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-04
Publication Date
2025-01-14
Estimated Expiration
2043-04-04

AI Technical Summary

Technical Problem

The existing antibiotic-contaminated water treatment catalysts have limited their application in catalyzing the advanced oxidation treatment of antibiotic pollution due to their strong metal leaching activity, small specific surface area of ​​materials and limited pH range.

Method used

The mesoporous titanium oxide supported by the preparation method of a high-content cobalt single-atom catalyst was prepared by the sol-gel method, and the cocatalysis between the oxide support and the metal cobalt single-atom catalyst was prepared by the sol-gel method. Synergistic effect improves charge transfer rate and catalytic performance, and achieves efficient degradation of sulfasalazine.

Benefits of technology

This method improves the advanced oxidation activation efficiency of persulfate of the catalyst, optimizes the interface cocatalytic effect, enhances structural stability and electron transfer efficiency, and achieves efficient degradation of antibiotic pollutants, with good environmental friendliness and application prospects .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116212876B_ABST
    Figure CN116212876B_ABST
Patent Text Reader

Abstract

The present invention discloses a preparation method and application of a mesoporous titanium oxide-supported high-content cobalt single-atom catalyst. Tetrabutyl titanate is used as a precursor, polyether is used as a template, and a mesoporous titanium oxide-supported high-content cobalt single-atom catalyst is successfully prepared by a sol-gel one-pot method. The catalyst prepared by the present invention not only effectively overcomes the disadvantages of unstable co-catalytic effect of oxide carrier and supported metal cobalt and small surface area of ​​block material, but also solves the problem of low loading of cobalt single atoms that are easy to cluster. The preparation method of the present invention is simple, low-cost and universal. The prepared catalyst has strong applicability, mild reaction conditions, and excellent catalytic activation persulfate advanced oxidation reaction performance for degradation of antibiotic sulfasalazine, and the mesoporous titanium oxide-supported high-content cobalt single-atom catalyst after five degradation cycles of antibiotic sulfasalazine still maintains good structure and catalytic performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of preparation of high-loaded single-atom catalytic materials, and specifically relates to a preparation method and application of a mesoporous titanium oxide-loaded high-content cobalt single-atom catalyst. Background Art

[0002] With the increasing application of antibiotic compounds, more and more antibiotics are discharged into the water environment, posing a threat to human health and the ecological environment, and becoming an environmental problem that cannot be ignored. In the field of sulfonamide antibiotic pollutant treatment, activated persulfate advanced oxidation technology has received widespread attention. In recent years, carbon nitride, graphene and carbon nanotubes have been used as carriers to improve transition metal defects. The catalysts thus formed have been widely used in advanced oxidation treatment of water pollution due to their good economy and relatively stable chemical structure. However, their strong metal leaching activity, small material specific surface area, and limited pH application range have limited their practical application in catalytic activated persulfate advanced oxidation treatment of antibiotic pollution. In order to overcome this problem, various morphology and composition modification strategies have been proposed, among which metal oxide-supported transition metal single atom catalysts have attracted attention due to their high metal utilization, excellent activation performance and stable co-catalytic effect. However, how to prepare mesoporous materials loaded with high-content metal single atom catalysts has become a difficult problem in the field of advanced oxidation antibiotic pollution treatment. Summary of the invention

[0003] In order to solve the above technical problems, the present invention provides a mesoporous titanium oxide-loaded high-content cobalt single-atom catalyst, which has high degradation efficiency for the antibiotic sulfasalazine and stable catalytic performance.

[0004] On the one hand, the present invention provides a method for preparing a mesoporous titanium oxide-supported high-content cobalt single-atom catalyst, the specific steps of which are as follows:

[0005] (1) Add tetrabutyl titanate and cobalt nitrate hexahydrate into a beaker, and add anhydrous ethanol and continue stirring until the solution becomes transparent and uniform, to obtain solution A;

[0006] (2) Add polyoxyethylene-polyoxypropylene block copolymer into a beaker, and add anhydrous ethanol and continue stirring until the solution becomes transparent and uniform, to obtain solution B;

[0007] (3) slowly dripping the solution B obtained in step (2) into the solution A obtained in step (1), and continuously stirring to obtain a uniform sol;

[0008] (4) drying the uniform sol obtained in step (3) in an oven to volatilize the solvent and obtain a dry solid;

[0009] (5) Grinding the dried solid obtained in step (4) and then calcining it to obtain the mesoporous titanium oxide-supported high-content cobalt single-atom catalyst.

[0010] Preferably, the mass ratio of cobalt nitrate hexahydrate to the precursor tetrabutyl titanate in step (1) is 0.01-0.07:1, and the stirring time is 0.5-1.0h.

[0011] Preferably, the mass ratio of the polyoxyethylene-polyoxypropylene block copolymer in step (2) to the precursor tetrabutyl titanate in step (1) is 0.1-0.2:1, and the stirring time is 0.5-1.0h.

[0012] Preferably, the stirring time of the mixed sol obtained in step (3) is 1.0-2.0 h.

[0013] Preferably, in step (4), the temperature of the oven is 65-100° C. and the drying time is 18-24 hours.

[0014] Preferably, the calcination temperature in step (5) is 400-550°C, the heating rate is 5-15°C / min, and the calcination time is 3-5h.

[0015] On the other hand, the present invention provides the use of the mesoporous titanium oxide-supported high-content cobalt single-atom catalyst prepared by the preparation method in catalytic degradation of the antibiotic sulfasalazine.

[0016] The present invention prepares a mesoporous titanium oxide-supported high-content cobalt single-atom catalyst by a sol-gel one-pot method, resulting in a co-catalytic synergistic effect between the oxide carrier and the metal cobalt single atom, thereby increasing the charge transfer rate and effectively improving the catalytic performance of the material. The catalyst obtained by the preparation method provides abundant metal cobalt single-atom active sites, increases the activation efficiency of persulfate, and realizes the efficient catalytic degradation of sulfasalazine by the activated persulfate advanced oxidation reaction.

[0017] The polyoxyethylene-polyoxypropylene block copolymer described in the present application is polyether F127 produced by McLean.

[0018] The beneficial effects of the present invention are:

[0019] (1) The raw materials of the present invention are widely available and of low cost; the preparation process is simple, mild, green and safe.

[0020] (2) Compared with the original titanium oxide carrier, the present invention anchors and loads high-content cobalt single atoms through the sol-gel method. The combination of the material phase clearly shows that this supported single-atom structure can optimize the interface co-catalytic effect, reduce mass transfer resistance, increase the material specific surface area, enhance pollutant adsorption, improve structural stability, improve electron transfer efficiency, and increase single-atom active sites, thereby improving the persulfate advanced oxidation activation efficiency of the catalyst and achieving efficient degradation of sulfasalazine.

[0021] (3) The present invention opens up a new way to rationally design supported single-atom catalysts, improve electron transfer efficiency and enhance the performance of catalytic persulfate advanced oxidation degradation of pollutants.

[0022] (4) The catalyst prepared by the present invention exhibits efficient and stable advanced oxidation water treatment catalytic performance, has good environmental friendliness, and has good application prospects in treating the antibiotic pollutant sulfasalazine. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The XRD patterns of the catalysts prepared in Example 1, Example 2, Comparative Example 1 and Comparative Example 2;

[0024] Figure 2 TEM images of the catalysts prepared in Example 1, Example 2, Comparative Example 1 and Comparative Example 2;

[0025] Figure 3 It is the XPS spectra of O1s in the catalysts prepared in Example 1, Example 2 and Comparative Example 1;

[0026] Figure 4 It is a diagram showing the effect of the catalysts prepared in Example 1, Example 2, Example 3, Comparative Example 1 and Comparative Example 2 catalytically degrading the antibiotic sulfasalazine under light-proof conditions;

[0027] Figure 5 0.10Co prepared in Example 1 SA / Activity diagram of TiO2 catalytic degradation of antibiotic sulfasalazine under light-protected conditions. DETAILED DESCRIPTION

[0028] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only some embodiments of the present invention, rather than all embodiments. The experimental methods in the following embodiments that do not specify specific conditions are usually operated under conventional conditions. Unless otherwise defined, all practical professional and scientific terms described in the text have the same meanings as those familiar to those skilled in the art.

[0029] Example 1 A Mesoporous Titanium Oxide Supported Cobalt Single Atom Catalyst

[0030] The preparation method comprises the following steps:

[0031] (1) First, weigh 7.50 g of tetrabutyl titanate and 0.46 g of cobalt nitrate hexahydrate, and at the same time, weigh 30 ml of anhydrous ethanol to dissolve and stir for 0.5 h until the solution becomes homogeneous and transparent, to obtain solution A;

[0032] (2) Weigh 1.21 g of polyoxyethylene-polyoxypropylene block copolymer and 15 ml of anhydrous ethanol and stir for 0.5 h until the mixture becomes homogeneous and transparent to obtain solution B;

[0033] (3) Slowly dripping solution B prepared in step (2) into solution A prepared in step (1), stirring continuously for 1.5 h until a uniform sol is obtained;

[0034] (4) drying the uniform sol obtained in step (3) in an oven at 65° C. for 20 h to evaporate the solvent and obtain a dry solid;

[0035] (5) The dried solid obtained in step (4) was ground and placed in a muffle furnace for calcination. The temperature was increased at a rate of 10°C / min and calcined at 550°C for 4 h to obtain a sample with a Co mass fraction of 10 wt%, which was recorded as 0.10Co SA / TiO2 supported single atom catalyst.

[0036] Example 2 A Mesoporous Titanium Oxide Supported Cobalt Single Atom Catalyst

[0037] The preparation method is basically the same as that of Example 1, except that: in step (1), the mass of cobalt nitrate hexahydrate is 0.09 g, the mass of tetrabutyl titanate is 9 g, the mass ratio of cobalt nitrate hexahydrate to tetrabutyl titanate is 0.01:1, and a sample with a Co mass fraction of 2 wt% is obtained, which is recorded as 0.02Co SA / TiO2 supported single atom catalyst.

[0038] Example 3 A mesoporous titanium oxide supported cobalt single atom catalyst

[0039] The preparation method is basically the same as that of Example 1, except that:

[0040] The mass of tetrabutyl titanate in step (1) is 7.50 g, the mass ratio of cobalt nitrate hexahydrate to tetrabutyl titanate in step (1) is 0.03:1, and the stirring time is 1.0 h;

[0041] The mass ratio of the polyoxyethylene-polyoxypropylene block copolymer in step (2) to the precursor tetrabutyl titanate in step (1) is 0.1:1, and the stirring time is 1.0 h;

[0042] The stirring time in step (3) is 2.0 h;

[0043] In step (4), the temperature of the oven is 100° C. and the drying time is 24 h;

[0044] The calcination temperature in step (5) is 400° C., the heating rate is 5° C. / min, and the calcination time is 3 h.

[0045] The sample 0.06Co with a Co mass fraction of 6wt% was obtained. SA / TiO2 supported single atom catalyst.

[0046] Comparative Example 1 A catalyst

[0047] The preparation method is basically the same as that of Example 1, and the difference from Example 1 is that in step (1), cobalt nitrate hexahydrate is not added, and is recorded as TiO2 catalyst.

[0048] Comparative Example 2 A catalyst

[0049] The preparation method is basically the same as that of Example 1, except that 1.15 g of cobalt nitrate hexahydrate is added in step (1), and the metal cobalt clusters form nanoparticles, which do not exist in the form of independent single atoms, and are recorded as Co nano / TiO2 catalyst.

[0050] Figure 1 The XRD diagrams of the catalysts prepared in Example 1, Example 2, Comparative Example 1 and Comparative Example 2 are shown below. SA / TiO2 and 0.10Co SA All the main peaks of the original TiO2 can be found in the XRD curve of / TiO2, and no peak representing metallic cobalt appears, proving that 0.02Co SA / TiO2 and 0.10Co SA There are no clusters of metallic cobalt in / TiO2, and no nanoparticles. nano The main peak representing CoTiO2 appeared in the XRD curve of / TiO2, proving that Co nano The metallic cobalt in / TiO2 forms oxides in the form of nanoclusters.

[0051] Figure 2 TEM images of the catalysts prepared in Example 1, Example 2, Comparative Example 1 and Comparative Example 2.

[0052] Figure a is a TEM (HAADF-STEM) image of the catalyst prepared in Example 2, in which isolated cobalt single atom bright spots are marked with red circles, showing uniformly dispersed Co single atoms without the appearance of Co clusters; Figure b is a TEM (HAADF-STEM) image of the catalyst prepared in Example 1, in which isolated cobalt single atom bright spots are marked with red circles, showing uniformly dispersed Co single atoms without the appearance of Co clusters. The distribution of cobalt single atoms in Figure b is denser than that in Figure a, indicating that 0.10Co SA / Co single atom loading in TiO2 is greater than 0.02Co SA / TiO2; Figure c is a TEM image of the catalyst prepared in Example 2, Co nano / The metal cobalt clusters in TiO2 form nanoparticles and do not exist in the form of independent single atoms; Figure d is a TEM image of the catalyst prepared in Example 1, showing TiO2 anatase lattice fringes and no metal cobalt loading.

[0053] Figure 3 The XPS spectra of O1s in the catalysts prepared in Example 1, Example 2 and Comparative Example 1 show that all samples show similar energy spectra, corresponding to lattice oxygen and oxygen vacancies in the form of -OH on the surface of the titanium oxide carrier. The peak value only moves slightly to a lower energy level with the increase of the mass fraction of the loaded metal cobalt.

[0054] Example 4

[0055] Performance test of degradation of sulfasalazine by persulfate advanced oxidation catalysis:

[0056] All degradation reactions were carried out in 100 mL glass bottles, and the initial concentration of sulfasalazine in the reaction solution was set to 2 μM. The pH value of the solution was adjusted with sulfuric acid (50 mM) and sodium hydroxide (50 mM). 50 mg of the catalyst prepared in the above Example 1, Example 2, Example 3, Comparative Example 1, and Comparative Example 2 were added respectively, and the reaction solution was stirred in the dark for 30 min. After reaching adsorption equilibrium, persulfate was added to initiate the degradation reaction. Next, during the reaction process, 0.5 mL of the reaction solution was aspirated with a syringe at designated time points of 5 min, 10 min, 20 min, 30 min, 40 min, 50 min, and 60 min, and immediately filtered with a 0.22 μm, polytetrafluoroethylene filter. Residual oxidized substances were quenched with sodium thiosulfate solution. The concentration of sulfasalazine was determined by high performance liquid chromatography (HPLC, PerkinElmer Flexar, USA) and a C18 chromatographic column (4.6×150 mm, 5 μm, PerkinElmer, USA). From Figure 4It can be seen that Example 1 can almost completely catalyze the degradation of sulfasalazine within 10 minutes. After 60 minutes of reaction, the catalytic degradation efficiency of sulfasalazine prepared by Example 1, Example 2, Example 3, Comparative Example 1, and Comparative Example 2 is 100% (0.10Co SA / TiO2), 98.7%(0.02Co SA / TiO2), 99.3%(0.06Co SA / TiO2)、87.8%(TiO2)、91.7%(Co nano / TiO2). The mesoporous titanium oxide-loaded high-content cobalt single-atom catalyst prepared in the present application has a much higher efficiency in catalytic degradation of pollutants than the catalysts provided in Comparative Examples 1 and 2.

[0057] The initial concentration of sulfasalazine in the reaction solution was set to 2 μM. The pH value of the solution was adjusted with sulfuric acid (50 mM) and sodium hydroxide (50 mM). 50 mg of the mesoporous titanium oxide-supported high-content cobalt single-atom catalyst 0.10 Co prepared in Example 1 was added. SA / TiO2, the reaction solution was stirred in the dark for 30 minutes to reach adsorption equilibrium, and five cycles were conducted at room temperature, each reaction time was 70 minutes. After the fifth cycle test, the degradation efficiency of sulfasalazine still reached 91.1%.

[0058] Example 5

[0059] 0.02Co was tested according to the method of Example 4 SA / TiO2、0.06Co SA / TiO2, TiO2 activated degradation of sulfasalazine catalytic performance. After 70min of reaction under dark conditions, 0.02Co SA The degradation efficiency of / TiO2 catalyst for sulfasalazine was 98.7%, and after five cycles, its degradation efficiency for sulfasalazine was still 90.2%. After 70 minutes of reaction under dark conditions, 0.06Co SA The degradation efficiency of the TiO2 catalyst for sulfasalazine is 99.3%. After five cycle tests, the degradation efficiency of the catalyst for sulfasalazine is still 91.0%.

[0060] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention. In addition, the technical solutions between the various embodiments can be combined with each other, but it must be based on the ability of ordinary technicians in the field to implement; when the combination of technical solutions is contradictory or cannot be implemented, it should be considered that such a combination of technical solutions does not exist and is not within the protection scope required by the present invention.

Claims

1. A method for preparing a mesoporous titanium oxide-supported high-content cobalt single-atom catalyst, characterized in that: The specific steps include: (1) Add tetrabutyl titanate and cobalt nitrate hexahydrate into a beaker, and add anhydrous ethanol and continue stirring until the solution becomes transparent and uniform, to obtain solution A; (2) Add polyoxyethylene-polyoxypropylene block copolymer into a beaker, and add anhydrous ethanol and continue stirring until the solution becomes transparent and uniform, to obtain solution B; (3) slowly dripping the solution B prepared in step (2) into the solution A prepared in step (1), and continuously stirring to obtain a uniform sol; (4) drying the uniform sol obtained in step (3) in an oven to volatilize the solvent and obtain a dry solid; (5) Grinding the dried solid obtained in step (4) and then calcining it to obtain the mesoporous titanium oxide-supported high-content cobalt single-atom catalyst.

2. The method for preparing a mesoporous titanium oxide-supported high-content cobalt single-atom catalyst according to claim 1, characterized in that: The mass ratio of cobalt nitrate hexahydrate to tetrabutyl titanate in step (1) is 0.01-0.07:

1.

3. The method for preparing a mesoporous titanium oxide-supported high-content cobalt single-atom catalyst according to claim 1, characterized in that: The mass ratio of the polyoxyethylene-polyoxypropylene block copolymer in step (2) to the tetrabutyl titanate in step (1) is 0.1-0.2:

1.

4. The method for preparing a mesoporous titanium oxide-supported high-content cobalt single-atom catalyst according to claim 1, characterized in that: In step (4), the temperature of the oven is 65-100° C. and the drying time is 18-24 hours.

5. The method for preparing a mesoporous titanium oxide-supported high-content cobalt single-atom catalyst according to claim 1, characterized in that: The calcination temperature in step (5) is 400-550°C, the heating rate of the calcination is 5-15°C / min, and the calcination time is 3-5h.

6. Use of the mesoporous titanium oxide-supported high-content cobalt single-atom catalyst prepared by the method for preparing the mesoporous titanium oxide-supported high-content cobalt single-atom catalyst according to any one of claims 1 to 5 in catalytic degradation of the antibiotic sulfasalazine.

Citation Information

Patent Citations

  • Monatomic loaded photo-titanium dioxide catalytic material and preparation method thereof

    CN112717908A

  • Monatomic cobalt-loaded tubular carbon nitride catalyst as well as preparation method and application thereof

    CN114534759A